Identification and impact of microbiota-derived metabolites in ascites of ovarian and gastrointestinal cancer - Sisi Deng; Wooyong Kim; Kefan Cheng; Qianlu Yang; Yogesh Singh; Gyuntae Bae; Nicolas Bézière; Lukas Mager; Stefan Kommoss; Jannik Sprengel; Christoph Trautwein (Cancer & Metabolism)
Abstract Background Malignant ascites is a common complication of advanced ovarian cancer (OC) and gastrointestinal cancer (GI), significantly impacting metastasis, quality of life, and survival. Increased intestinal permeability can lead to blood or lymphatic infiltration and microbial translocation from the gastrointestinal or uterine tract. This study aimed to identify microbiota-derived metabolites in ascites from OC (stages II-III and IV) and GI patients, assessing their roles in tumor progression. Methods Malignant ascites samples from 18 OC and GI patients were analyzed using a four-dimensional (4D) untargeted metabolomics approach combining reversed-phase (RP) and hydrophilic interaction liquid chromatography (HILIC) with trapped ion mobility spectrometry time-of-flight mass spectrometry (timsTOF-MS). Additonally, a targeted flow cytometry-based cytokine panel was used to screen for inflammatory markers. Non-endogenous, microbiota-derived metabolites were identified through the Human Microbial Metabolome Database (MiMeDB). Results OC stage IV exhibited metabolic profiles similar to GI cancers, while OC stage II-III differed significantly. Stage IV OC patients exhibited higher levels of 11 typically microbiome-derived metabolites, including 1-methylhistidine, 3-hydroxyanthranilic acid, 4-pyridoxic acid, biliverdin, butyryl-L-carnitine, hydroxypropionic acid, indole, lysophosphatidylinositol 18:1 (LPI 18:1), mevalonic acid, N-acetyl-L-phenylalanine, and nudifloramide, and lower levels of 5 metabolites, including benzyl alcohol, naringenin, o-cresol, octadecanedioic acid, and phenol, compared to stage II–III. Correlation analysis revealed positive associations between IL-10 and metabolites such as glucosamine and LPCs, while MCP-1 positively correlated with benzyl alcohol and phenol. Conclusion 4D metabolomics revealed distinct metabolic signatures in OC and GI ascites, highlighting microbiota-derived metabolites involved in lipid metabolism and inflammation. Metabolites like 3-hydroxyanthranilic acid, indole, and naringenin may serve as markers of disease progression and underscore the microbiota’s role in shaping malignant ascites and tumor biology.